Strain-Induced Surface Roughening in Polycrystalline VT1-0 Titanium Specimens under Uniaxial Tension; Physical Mesomechanics; Vol. 21, iss. 3 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Romanova V. A. Varvara Aleksandrovna; Balokhonov R. R. Ruslan Revovich; Kozelskaya A. I. Anna Ivanovna; Sinyakova E. A. Elena Aleksandrovna; Krukovsky K. V. Konstantin Vitaljevich (2018, 2018)
Title screen